2012
DOI: 10.1002/agr.21292
|View full text |Cite
|
Sign up to set email alerts
|

Do Inventories Have an Impact on Price Transmission? Evidence From the Canadian Chicken Industry

Abstract: This paper investigates the influence of inventories in explaining the magnitude of price transmission. The empirical strategy consists of two distinct steps. First, the flexible nonlinear framework of Hamilton is used to investigate the influence of inventories on price transmission. The procedure detects significant non-linearities and suggests that the price transmission elasticity is increasing in the level of the farm price and decreasing in the ratio of inventories to sales. This evidence leads to specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Using a theoretical model, Reagan and Weitzman (1982) suggested that inventory management strategies of market actors could lead to APT. Such a relationship has been empirically confirmed for the Canadian chicken industry (Abbassi et al, 2012) and American beef industry (Surathkal and Chung, 2019).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Using a theoretical model, Reagan and Weitzman (1982) suggested that inventory management strategies of market actors could lead to APT. Such a relationship has been empirically confirmed for the Canadian chicken industry (Abbassi et al, 2012) and American beef industry (Surathkal and Chung, 2019).…”
mentioning
confidence: 71%
“…5.2.2 Inventory behavior. Inventory behavior also plays a role in APT (Roberts et al, 1994;Meyer and Cramon-Taubadel, 2004;Abbassi et al, 2012). According to our survey result, the distribution of the inventory period in Kano is concentrated in the lower left side of Figure 5 compared with Ibadan, implying that the inventory period in Kano is shorter.…”
mentioning
confidence: 75%
“…Several recent agricultural commodity price transmission and market integration studies have focused on price relationships among markets for which trade regularly occurs (see the methodological development and worldwide empirical evidence of agricultural commodity price transmission in Brosig et al (2011), Abbassi et al (2012), Tekgüç (2013), Acosta et al (2014), Santeramo (2015), Cacchiarelli et al (2016), Tifaoui and Von Cramon‐Taubadel (2017), and Yu and Gould (2019)). Most of these studies have a similar underlying theoretical competitive spatial equilibrium framework, which is described thoroughly by Lence et al (2018).…”
Section: Literature Review: Price Transmission With Growing Conditions Variation and Sparse Market Informationmentioning
confidence: 99%
“…Thus, the way the product prices are transmitted throughout the marketing chain is traditionally a matter of concern (Bor et al, 2014;Guillen and Artés, 2015;Hahn et al, 2016). However, this issue has frequently been addressed within its aspect of the determination of the transmission between farmer-retailer-consumer prices (Ben- Kaabia, et al, 2005;Abbassi et al, 2012;Rezitis, 2012) instead of examining the right price transmission from the feed to the livestock market (Brümmer et al, 2009;De and Zhou, 2015).…”
Section: Literaturementioning
confidence: 99%